COMMUNITY PERCEPTIONS ABOUT IN-VITRO MEAT OR ARTIFICIAL MEAT ON HEALTH AS A FOOD SOURCE SOLUTION FOR THE FUTURE (Jurnal Nutrire Diaita (Ilmu Gizi), 2023)
In vitro meat production systems involve the raising of stem cells extracted from farm animals in the bioreactor and using modern tissue engineering techniques to produce meat outside animal feed. The question in this study is "how is the perception of in-vitro meat or artificial meat towards health a solution to future food sources?" The research method used is a descriptive qualitative method, the data collection technique for surveys, by spreading a questionnaire in the form of a Google form link through social media such as whatsapp, email, and facebook. Questionnaires charge for 10 days and study subjects of nutritionists who work in hospitals, health sudin, and lecturer (51 respondents). Results showed that 71% (36) respondents knew in-vitro meat (artificial meat), from Google (29%), youtube (27%) and 22% (11 people) did not know about in-vitro meat. The majority of respondents (61% or 31) responded that in-vitro meat was unsafe to human consumption, and did not approve of whether it was on the market in Indonesia (57% or 29). The conclusion from this study suggests that uncertainty about artificial meat in society, the need to be educated about in-vitro meat (artificial meat), finally the public perception that it is not simply to accept foods made in the laboratory by using a tekzeroKeywords: Artificial meat, In-Vitro Meat, cultivation, people, opinion, reaction